2022
DOI: 10.1038/s41590-022-01355-3
|View full text |Cite
|
Sign up to set email alerts
|

Distinct changes in endosomal composition promote NLRP3 inflammasome activation

Abstract: Inflammasome complexes are pivotal in the innate immune response. The NLR family pyrin domain containing protein 3 (NLRP3) inflammasome is activated in response to a broad variety of cellular stressors. However, a primary and converging sensing mechanism by the NLRP3 receptor initiating inflammasome assembly remains ill defined. Here, we demonstrate that NLRP3 inflammasome activators primarily converge on disruption of endoplasmic reticulum–endosome membrane contact sites (EECS). This defect causes endosomal a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
73
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(95 citation statements)
references
References 38 publications
22
73
0
Order By: Relevance
“…These data suggest that NLRP3 can localize to multiple endolysosomal membranes upon stimulation, consistent with a previous report of colocalization of TGN38, EEA1, and NLRP3-GFP in nigericintreated HeLa cells (5). Furthermore, as presented in a related study, activated NLRP3 localizes to RAB5-positive endosomes after stimulation (26).…”
Section: Nlrp3 Can Localize To Membranes Of Endolysosomal Originsupporting
confidence: 92%
See 2 more Smart Citations
“…These data suggest that NLRP3 can localize to multiple endolysosomal membranes upon stimulation, consistent with a previous report of colocalization of TGN38, EEA1, and NLRP3-GFP in nigericintreated HeLa cells (5). Furthermore, as presented in a related study, activated NLRP3 localizes to RAB5-positive endosomes after stimulation (26).…”
Section: Nlrp3 Can Localize To Membranes Of Endolysosomal Originsupporting
confidence: 92%
“…Furthermore, NLRP3 can interact with PI4P through a conserved polybasic motif (5), and endosomal membranes contain this lipid (28). A related study reports NLRP3 recruitment to PI4P-containing endosomes (26). PI4P seems likely to be important for NLRP3 membrane recruitment but may not be the only factor.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This likely reflects effects of polymorphonuclear architecture to favor formation of multiple specks adjacent to individual lobes of the atypical nucleus. Recent studies in macrophages have also demonstrated that the initial formation of NLRP3 oligomers is seeded at discrete endosomal loci 194,195 . As discussed in Section 5.1, neutrophils containing activated NLRP3 inflammasomes are particularly resistant to pyroptosis 31,33,51,57 with delayed lysis in only a small percentage of cells 75 .…”
Section: Integrated Model For How Different Inflammasome Signaling Pl...mentioning
confidence: 98%
“…For example, (1) CatB involves in the activation of NFκB, which is responsible for the transcriptional regulation of NLRP3 and IL-1β; (2) Mitochondrial ROS is one of the key factors for NLRP3 activation, and we have reported that leaked CatB in the cytosol could induce mitochondrial ROS production [ 12 ]; (3) NLRP3 inflammasome was reported to be activated on the dispersed trans-Golgi network where CatB has the chance to interact with NLRP3 inflammasome [ 22 , 23 ]. (4) A new finding suggested that the vesicles to which NLRP3 is recruited are of endosomal origin [ 24 ]. It is reasonable to assume that CatB may activate NLRP3 inflammasome in the endosomes.…”
Section: Cathepsin B In Pcdmentioning
confidence: 99%